1996
DOI: 10.1093/clinids/22.2.336
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole-Induced Congenital Anomalies in Three Infants

Abstract: Fluconazole has been associated with various teratisms in animals, including craniofacial ossification defects, thin, wavy ribs, and renal pelvis defects. We describe three infants born to women who were receiving fluconazole through or beyond the first trimester of pregnancy. All of the infants had congenital anomalies; no other drug was implicated. Only one of the three infants survived. Their anomalies, similar to those observed in animal studies, were largely craniofacial, skeletal (i.e., thin, wavy ribs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
128
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(130 citation statements)
references
References 12 publications
2
128
0
Order By: Relevance
“…The same 22-year old mother described by Lee et al 11 had two subsequent pregnancies that were reported by Pursley et al 12 in 1996. During her third pregnancy, the patient was nonadherent to therapy, delivered a healthy boy, and resumed FLU therapy.…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…The same 22-year old mother described by Lee et al 11 had two subsequent pregnancies that were reported by Pursley et al 12 in 1996. During her third pregnancy, the patient was nonadherent to therapy, delivered a healthy boy, and resumed FLU therapy.…”
mentioning
confidence: 53%
“…9 In August 2011, the U.S. Food and Drug Administration (FDA) issued a safety announcement concerning the use of FLU in pregnancy. On the basis of several published case reports in humans [11][12][13][14] , and animals showing similar causative effects 15 , the FDA changed the pregnancy category of FLU from category C to category D for all indications except FLU 150 mg as a single dose for treatment of vaginal candidiasis, citing trends of "a rare and distinct set of birth defects in infants whose mothers were treated with the drug during the first trimester of pregnancy".included a short, broad head, abnormal looking face, abnormal development of the skullcap, oral cleft, bowing of the thigh bones, thin ribs and long bones, muscle weakness and joint deformities, and congenital heart disease. 16 Created in 1980, the FDA's drug-associated pregnancy risk categories, which consist of the letter designations of A, B, C, D, or X, are assigned according to the known or potential fetal harm associated with drug therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the potential teratogenic effect of drugs used for the treatment of maternal VV-BV during pregnancy was frequently evaluated. For example the high dose of fluconazole [11,12] was found to be teratogenic in human beings.…”
Section: Introductionmentioning
confidence: 99%